Element contents changes during the propagule development of two Sonneratia species - Liu, Chao; Zhang, Lin; Shi, Xiaofang; Tang, Yanna; Wang, Mao; Wang, Wenqing (Frontiers in Marine Science, 2025)
Vivipary is common in several mangrove species and is generally considered an adaptation to the intertidal saline environment. However, the coexistence of many nonviviparous mangroves makes this view controversial. This study investigated the propagule development of two nonviviparous mangrove species, Sonneratia alba and S. caseolaris, with marked differences in salt tolerance and distribution. Changes in the density, water content, and concentrations of the five main osmoregulatory elements (Cl, Na, K, Ca, and Mg) were determined. As the propagules of S. alba and S. caseolaris mature, the element concentrations (mg/g) in the propagules gradually decrease, indicating a desalination process. Moreover, the Cl, Na, Ca, and Mg content in the propagules were lower than in the mature leaves and calyx. Similar to viviparous mangroves, the development of the propagules of nonviviparous mangroves is also a desalination process. Although both viviparous and nonviviparous mangrove species undergo a desalination process during propagule development, our findings suggest that viviparity may not be solely defined by desalination, but rather by the extended period of low-salinity protection during early development on the maternal tree, which represents a key adaptation for survival in high-salinity environments. In contrast, nonviviparous mangroves, which rely on seed germination and early development in saline seawater, face additional challenges in high-salinity habitats, highlighting their distinct adaptive strategies.